Carbon emission reduction accounting in cathode material recycling of power batteries from a multiple-life-cycle perspective - TIAN Xi, MA Qingyuan, XIE Jinliang, HU Zhikang, XU Ming, PENG Fei, PENG Aiping (Ziyuan Kexue)
[Objective] Resource recycling of end-of-life battery cathode materials has carbon emission reduction potential, but existing studies show significant deviations in emission reduction calculations due to unclear accounting boundaries. This study develops an improved accounting method for carbon emission reduction from the perspective of multiple-life-cycle resource cycling. [Methods] Using virgin material substitution as the baseline scenario, the energy consumption and auxiliary material emissions during resource utilization were incorporated. The method emphasized that recycling only delayed rather than avoided carbon emissions from final disposal, thus excluding final disposal from accounting boundaries. The carbon emission reduction from recycling 1 ton of cathode materials was quantified through four recycling processes for lithium iron phosphate and ternary lithium batteries. [Results] (1) Compared with scenarios of “virgin material substitution combined with incineration disposal” and “virgin material substitution combined with landfill disposal”， the carbon emission reductions from recycling processes decreased by 0.80 t CO2 eq and 7.96 t CO2 eq, respectively, when “virgin material substitution” was adopted as the baseline. This indicated that including final disposal (landfill or incineration) in the baseline scenario substantially overestimated carbon emission reduction benefits. (2) Both the slurry acid leaching process for lithium iron phosphate and the acid leaching-extraction process for ternary lithium batteries demonstrated carbon reduction benefits. Notably, the ternary lithium batteries achieved carbon emission reductions 10 times higher than those of lithium iron phosphate due to recoverable high-value metals like nickel and cobalt. (3) The calcination-acid leaching process resulted in a higher carbon footprint for the recycled materials than that of virgin materials owing to the substantial emissions from auxiliary material (e.g., citric acid) production. [Conclusion] In summary, the baseline scenario selected in this accounting method aligns more closely with current production realities domestically and internationally, facilitating the establishment of consistent standards for comparing resource recycling technologies within the industry. Furthermore, through analysis of the calculation results, “high-carbon” processes and the corresponding sensitive factors can be identified to guide process improvement.